2015
DOI: 10.4038/jpgim.7664
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Health Promotion Approach among Public Health Midwives in a District in Sri Lanka

Abstract: BackgroundThe Ottawa Charter defines Health Promotion as the 'process of enabling people to increase control over, and to improve, their health'. The National Health Promotion Policy recognizes health promotion as an efficient and cost effective approach to promote health in Sri Lanka. The Public Health Midwife (PHM) is the grass root level health worker responsible for promoting the health of communities in Sri Lanka. Their knowledge regarding health promotion has not been assessed. The main aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
2
9
1
Order By: Relevance
“…It is a proven fact that older age groups perform less in short-term memory, making it difficult for them to acquire and retrieve information ( 5 ). The PHMs who were trained on health promotion had a ‘good’ level of knowledge in contrast to the present study ( 6 ). The major areas that the PHM’s lacked knowledge in the present study were on reproductive tract infections and possible causes for pathological vulvo-vaginal discharge ( Table 1 ).…”
Section: Dear Editor-in-chiefcontrasting
confidence: 75%
“…It is a proven fact that older age groups perform less in short-term memory, making it difficult for them to acquire and retrieve information ( 5 ). The PHMs who were trained on health promotion had a ‘good’ level of knowledge in contrast to the present study ( 6 ). The major areas that the PHM’s lacked knowledge in the present study were on reproductive tract infections and possible causes for pathological vulvo-vaginal discharge ( Table 1 ).…”
Section: Dear Editor-in-chiefcontrasting
confidence: 75%
“…A survey done to identify essential public health functions of field health staff in Sri Lanka, indicated that PHMs accept that health promotion is a function applicable to their work [23]. However, the most stated perceived benefit of health promotion approach was that it makes the duties of a PHM easier which is contrary to the common belief that it increases the work load of PHMs, adding more burden to them [23]. Therefore the introduction of a tool to assess vaginal discharge will not be an additional burden to them, but will make their life easier.…”
Section: Practical Implications Of the Developed Vaginal Discharge Assessment Form In The Community Settingmentioning
confidence: 99%
“…However, they stated that health promotion principles were difficult to grasp and that their skills were insufficient for executing good health promotion programmes (Fernando et al,2006). According to a study conducted in Sri Lanka's Kandy area, the majority of PHMs (65.4 percent) had a poor understanding of health promotion (Perera, 2012).…”
Section: Introductionmentioning
confidence: 99%